Hypertensive Disorders of Pregnancy and Future Cardiovascular Health - Melchiorre, Karen; Thilaganathan, Basky; Giorgione, Veronica; Ridder, Anna; Memmo, Alessia; Khalil, Asma (Frontiers in Cardiovascular Medicine, 2020)
Hypertensive disorders of pregnancy (HDP) occur in almost 10% of gestations. These women present higher cardiovascular morbidity and mortality later in life in comparison with parous controls. This is not surprising as several studies already demonstrated that women with preeclampsia at acute disease in pregnancy present a state of segmental impaired myocardial contractility and relaxation, systo-diastolic biventricular chamber dysfunction, adverse biventricular remodeling/hypertrophy, disadvantageous hemodynamic state and indirect echocardiographic signs of localized myocardial ischemia and fibrosis. All of these cardiac functional and geometric changes are known to have strong predictive value for cardiovascular disease in non-pregnant subjects. A “dose effect” response seems to regulate this relationship with the worse cardiovascular profile in women with severe disease in pregnancy, early onset complication, coexistence of fetal growth disorders, need for iatrogenic preterm delivery and recurrence of HDP in subsequent pregnancies. The mechanism underlying the relationship between HDP in youth and cardiovascular disease later in life is unclear but it could be explained by their wide sharing pre-pregnancy cardiovascular risk factors or it may be due to a direct impact of the HDP on the maternal cardiovascular system favoring a state of increased susceptibility to future metabolic or hemodynamic insults. If so, the prevention of HDP itself would become all the more urgent. Shortly after delivery formerly HDP women express an increased risk of classic cardiovascular risk factors such as essential hypertension, renal diseases, abnormal lipid profile and diabetes with higher frequency than controls. Within the first decades after delivery this group of women experiences the occurrence of premature cardiovascular events, such as symptomatic heart failure, myocardial ischemia and cerebral vascular disease with a prevalence significantly higher than that of controls. Although there is general agreement that women who suffered from HDP should undertake early screening for cardiovascular risk factors in order to allow for appropriate prevention, the exact timing and modality of screening has not been standardized yet. Surely prevention should start as soon as early after delivery making the women aware of their increased cardiovascular risk and encouraging weight control, stop smoking, healthy diet and daily exercise which are cost-effectiveness prevention strategies.